The Microbial Ferrous Wheel in a Neutral pH Groundwater Seep - Roden, Eric; McBeth, Joyce M.; Blothe, Marco; Percak-Dennett, Elizabeth M.; Fleming, Emily J.; Holyoke, Rebecca R.; Luther, George W.; Emerson, David (Frontiers in Microbiology, 2012)
Evidence for microbial Fe redox cycling was documented in a circumneutral pH groundwater seep near Bloomington, Indiana. Geochemical and microbiological analyses were conducted at two sites, a semi-consolidated microbial mat and a floating puffball structure. In situ voltammetric microelectrode measurements revealed steep opposing gradients of O2 and Fe(II) at both sites, similar to other groundwater seep and sedimentary environments known to support microbial Fe redox cycling. The puffball structure showed an abrupt increase in dissolved Fe(II) just at its surface (~ 5 cm depth), suggesting an internal Fe(II) source coupled to active Fe(III) reduction. MPN enumerations detected microaerophilic Fe(II)-oxidizing bacteria (FeOB) and dissimilatory Fe(III)-reducing bacteria (FeRB) at densities of 102-105 cells mL-1 in samples from both sites. In vitro Fe(III) reduction experiments revealed the potential for immediate reduction (no lag period) of native Fe(III) oxides. Conventional full-length 16S rRNA gene clone libraries were compared withhigh throughput barcode sequencing of the V1, V4 or V6 variable regions of 16S rRNA genes in order to evaluate the extent to which new sequencing approaches could provide enhanced insight into the composition of Fe redox cycling microbial community structure. The composition of the clone libraries suggested a lithotroph-dominated microbial community centered around taxa related to known FeOB (e.g. Gallionella, Sideroxydans, Aquabacterium). Sequences related to recognized FeRB (e.g. Rhodoferax, Aeromonas, Geobacter, Desulfovibrio) were also well represented. Overall, sequences related to known FeOB and FeRB accounted for 88 and 59% of total clone sequences in the mat and puffball libraries, respectively. Taxa identified in the barcode libraries showed partial overlap with the clone libraries, but were not always consistent across different variable regions and sequencing platforms. However, the barcode libraries provided confirmatio